Mechanistic and Structural Understanding of Uncompetitive Inhibitors of Caspase-6 - Heise, Christopher E.; Murray, Jeremy; Augustyn, Katherine E.; Bravo, Brandon; Chugha, Preeti; Cohen, Frederick; Giannetti, Anthony M.; Gibbons, Paul; Hannoush, Rami N.; Hearn, Brian R.; Jaishankar, Priyadarshini; Ly, Cuong Q.; et al. (PLOS ONE, 2012)
Inhibition of caspase-6 is a potential therapeutic strategy for some neurodegenerative diseases, but it has been difficult to develop selective inhibitors against caspases. We report the discovery and characterization of a potent inhibitor of caspase-6 that acts by an uncompetitive binding mode that is an unprecedented mechanism of inhibition against this target class. Biochemical assays demonstrate that, while exquisitely selective for caspase-6 over caspase-3 and -7, the compound’s inhibitory activity is also dependent on the amino acid sequence and P1’ character of the peptide substrate. The crystal structure of the ternary complex of caspase-6, substrate-mimetic and an 11 nM inhibitor reveals the molecular basis of inhibition. The general strategy to develop uncompetitive inhibitors together with the unique mechanism described herein provides a rationale for engineering caspase selectivity.